„Sienkiewiczologowanie”. O Sienkiewiczowskich odniesieniach w powieściach Marii Pruszkowskiej - Rusin, Joanna (Tematy i Konteksty, 2019)
References to the work of H. Sienkiewicz in the work of M. Pruszkowska (1910–1973) appear in two of her novels: Prześlę panu list i klucz (I Will Send You a Letter and a Key) (1959) and Życie nie jest romansem, ale… (Life Is not a Love Affair, but…) (1964). The former depicts the fate of a book-loving Warsaw family in the 1930s. The parents and two daughters constantly use quotations in their conversations, which come from their favourite novels, most often from the Trilogy. The sisters make their lives theatrical by impersonating literary characters and competing in the best possible knowledge of Sienkiewicz’s texts. The other novel shows the same family during the Second World War. In the conditions of occupation, references to the favourite fragments of the Nobel Prize winner’s works often gain new and surprising significance. The literary excitement of Pruszkowska’s characters is analogous to the experiences of successive generations of Polish readers.